Sands of the soul - Whitney-Robinson, Voronica (Renton, Washington : Wizards of the Coast, 2002)
"The only legitimate daughter of the wealthy Uskevren family, Tazi has suffered blow after shattering blow to her body and her spirit, some at the hands of her most trusted allies."--Cover.
Keywords: Elves -- Fiction; Fantasy fiction